Analysis of the housing market in Lithuania - Ivanauskas, Feliksas; Eidukevičius, Rimantas; Marčinskas, Albinas; Galinienė, Birutė (International Journal of Strategic Property Management, 2010)
Cointegration and Granger causality tests were used for the statistical analyses of the housing market in Lithuania. The relationship between the cost of housing and afford‐ability on the one hand, and interest rates, GDP and average incomes on the other was not proven to exist using the given statistical methods. The period of increase in the cost of housing in Lithuania over the last five years is exceptional and difficult to explain using fundamental economic factors and their fluctuation trends alone. The cost of housing has made a clear departure from the economic (business) cycle; the economy has grown, however at a much slower rate than rising costs in the housing market. The reasons for this situation are record lows in interest rates, good conditions to gain financing, the liberalisation of financial markets, speculative attitudes in expectation of the introduction of the Euro, and a divide between the supply and demand of housing that is available. It should be noted that the evaluation of the influence of these factors on fluctuations in costs in the housing market is more hypothetical in nature.First published online: 18 Oct 2010